1999
DOI: 10.1111/1467-8624.00108
|View full text |Cite
|
Sign up to set email alerts
|

Communication Patterns of African American Girls and Boys from Low‐Income, Urban Backgrounds

Abstract: This study investigated gender effects on the conversational strategies used among 106 African American children ( mean age ϭ 7 years) from urban, low-income family backgrounds. Same-and mixed-gender pairs of children from the same grade level in an inner-city school were provided with toy bear puppets and asked to play together for 5 min. Conversations were coded using Leaper's Psychosocial Processes Coding Scheme, which classifies communication acts as either collaborative, controlling, informing, obliging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 63 publications
1
54
0
Order By: Relevance
“…Our findings for ratings of ''myself with a close same-sex peer'' suggest that the gender differentiation which develops in same-sex dyads and groups in childhood (Leaper, 1991;Leaper et al, 1999;Maccoby, 1998) persists in heightened form in this context into adolescence. The fact that this was the only role in which boys' assertive ratings were significantly higher than girls', however, suggests that general conclusions about gender differences should not be drawn from studies that only consider this context.…”
Section: Discussionmentioning
confidence: 67%
“…Our findings for ratings of ''myself with a close same-sex peer'' suggest that the gender differentiation which develops in same-sex dyads and groups in childhood (Leaper, 1991;Leaper et al, 1999;Maccoby, 1998) persists in heightened form in this context into adolescence. The fact that this was the only role in which boys' assertive ratings were significantly higher than girls', however, suggests that general conclusions about gender differences should not be drawn from studies that only consider this context.…”
Section: Discussionmentioning
confidence: 67%
“…There were no average differences in informing speech. Perhaps this should not be a surprise given this is a relatively neutral speech act (e.g., see Leaper, Tenenbaum, & Shaffer, 1999). Average gender differences were also negligible for directives and disagreements, which were surprising given that these were the most power-assertive speech forms.…”
Section: Operational Definitionmentioning
confidence: 96%
“…Some notable examples include task-oriented and socioemotional activity (Bales, 1950), instrumental and expressive behavior (Parsons & Bales, 1955), dominance and love (Leary, 1957), control and affection (Schutz, 1958), agency and communion (Bakan, 1966), power and affiliation (McClelland, 1987;Wiggins, 1973), and other-transforming and selftransforming orientations (Selman & Demorest, 1984), respectively. Although assertion and affiliation are not mutually exclusive psychological acts, they can be viewed as separate dimensions (see Leaper, 1991Leaper, , 1994Leaper, , 2000aLeaper, Tenenbaum, & Shaffer, 1999;Penman, 1980). According to this scheme, a speech act may be both assertive and affiliative when it is collaborative.…”
Section: Notesmentioning
confidence: 99%
“…Studies of children's interactions with peers suggest a different pattern, however. In one study, both boys and girls observed in same-age peer interactions used more affiliative speech with same-gender peers than in cross-gender interactions (Leman et al 2005), and in another, both boys and girls used a more affiliative style when the conversational partner was female (Leaper et al 1999). The most consistent findings of studies examining sex of child differences in parent speech are that mothers talk more with daughters than with sons and show more differentiation in their speech with daughters and sons than fathers do (Lanvers 2004).…”
Section: Introductionmentioning
confidence: 96%